Detection of Entamoeba histolytica, Giardia lamblia and Cryptospodium sp. Infection among diarrheal patients (Bangladesh Journal of Zoology, 2015)
Tri-combo ELISA tests were carried out to determine the prevalence of protozoan parasites (Entamoeba histolytica, Giardia lamblia and Cryptosporidium spp) in 1712 stool samples of diarhoeal patients. Among the samples tested, 118 (6.89%) were found positive. The age group 6-14 years were recorded to be more susceptible (14.81%) and prevalence gradually decreased as the age group increased. Individual Antigen Detection Tests were done on the positive samples and 1 sample was noted to carry E. histolytica (0.06%), 92 (5.37%) samples with G. lamblia and 22 (1.29%) samples with Cryptosporidium spp. Maximum prevalence was recorded in summer (8.47%) and rainy seasons (8.14%) and highest infections (10.46%) were found in the month of September The prevalence of G. lamblia was higher in male (5.37%) whereas, the prevalence of Cryptosporidium spp. was higher in female (1.64%).Bangladesh J. Zool. 43(1): 1-7, 2015